A missing link in family firms’ internationalization research: Family structures - Arregle, Jean-Luc; Hitt, Michael A.; Mari, Isabelle (Journal of International Business Studies, 2019)
Hennart, Majocchi, and Forlani propose and validate a new explanation of family firms’ internationalization heterogeneity shedding light on the role of a family firm’s global niche business model. This type of family firm can avoid the dominant internationalization problems usually depicted in the literature on family firms’ internationalization. Starting from the same diagnosis on extant research, we explore another perspective to explain this heterogeneity: the structure of the family institution. We examine the relationships of family structures, developed by Emmanuel Todd in social anthropology, to family firms’ internationalization. We explain how Todd’s typology of family structures can influence the new mechanisms proposed by Hennart and colleagues for family firms in Europe with a global niche business internationalization. Finally, using these family structures, we also reexamine two analyses on family firms’ internationalization. Therefore, we introduce a new perspective for research on family firms’ internationalization that is based on context and has critical importance for understanding family firms’ strategies. This new perspective has significance for international business research on family firms.